Revealing Intersectional Dynamics in Organizations: Introducing 'Intersectional Identity Work' - Atewologun, Doyin; Sealy, Ruth; Vinnicombe, Susan (Wiley, 2015)
Little consensus exists regarding conducting intersectional studies. We introduce ‘intersectional identity work’ as an approach for examining individuals’ experiences at the nexus of multiple identities. Incorporating identity work as a theoretical and analytical framework, we use journals and interviews to examine identity-heightening episodes that trigger meaning-making of intersecting senior, gender and ethnic identities among British Asian and black women and men. Our analysis reveals how intersecting identities are leveraged in encounters with subordinates, superiors and clients. Intersectional locations provide resources and cues for claiming or restricting privileged and disadvantaged status in asymmetric power positions. Intersectional identity work expands and restricts identification at juxtaposed locations. It offers a prospect for elucidating intersectional dynamics present in a range of identity configurations and addresses critiques that individual-level intersectional analyses at intersections are mere narrative. We encourage further research that examines other socially salient identities using our approach to develop theory on how multiple identities play out in everyday experience.
Keywords: intersectionality; identity work; methodology; ethnicity; gender